Frequency of Convergence Insufficiency in a Refraction Clinic of Karachi: Doi: 10.36351/pjo.v37i1.1131 - Urooj, Izmal; Ali, Shari Mussadiq; Ghayas, Abdul; Sheikh, Ammara; Hussain, Maryam (Pakistan Journal of Ophthalmology, 2020)
Purpose: To find out the frequency of convergence insufficiency in a refraction clinic of Karachi. Study Design: Cross Sectional Study. Place and Duration of Study: Al-Ibrahim Rye Hospital, Karachi from June to December 2019. Methods: A total of 150 patients were included in the study (52 males and 98 females). Patients with un-corrected visual acuity of ?6/9 and age between 16 – 35 years were included. Patients who had received treatment for convergence insufficiency (CI), mentally retarded patients, patients with Manifest strabismus or any other ocular pathology were excluded. Near point of convergence (NPC), near phoria and positive fusional vergence (PFV) were measured for the diagnosis of CI. Results: Mean age of the patients was 23.55 years. Gender wise distribution showed that 52 (34.7%) were males and 98 (65.3%) were females. Out of 150 patients, 64 patients had CI and 42 were normal with no reduction in NPC, PFV or exophoria. Rest of the patients had only one of the three criteria of CI but did not qualify our definition of CI. Twenty-five male patients and 39 female patients had CI. CI was more common in teenagers. With increasing age, the frequency of CI was reduced. CI due to remote NPC was seen in 12 (8%) and CI due to decreased PFV was seen in 21 (14%). Conclusion: Females are affected more with CI than males especially in the younger age group. Keywords: Convergence insufficiency, near point of convergence, Positive fusional vergence.